Paleogenomics of the prehistory of Europe: human migrations, domestication and disease - Javier G. Serrano; Alejandra C. Ordóñez; Rosa Fregel (Taylor & Francis Group, 2021)
A substantial portion of ancient DNA research has been centred on understanding European populations' origin and evolution. A rchaeological evidence has already shown that the peopling of Europe involved an intricate pattern of demic and/or cultural diffusion since the Upper Palaeolithic, which became more evident during the Neolithic and Bronze Age periods. However, ancient DNA data has been crucial in determining if cultural changes occurred due to the movement of ideas or people. With the advent of next-generation sequencing and population-based paleogenomic research, ancient DNA studies have been directed not only at the study of continental human migrations, but also to the detailed analysis of particular archaeological sites, the processes of domestication, or the spread of disease during prehistoric times. With this vast paleogenomic effort added to a proper archaeological contextualisation of results, a deeper understanding of Europe's peopling is starting to emanate.